The Contribution of Wrist Flexibility to Smash Accuracy in Volleyball Games Rajawali Club Athletes, Pelangiran District Indragiri Hilir Regency - hendra, hendra (FKIP Universitas Islam Indragiri, 2023)
This type of research is correlational. The population in this study were all volleyball athletes at Rajawali Club, Pelangi District, totaling 16 people. To obtain research data, tests and measurements were carried out, namely a protractor to measure wrist flexibility and to test the accuracy of volleyball smashes. Before being analyzed, the data normality test was first carried out with the Lilifors test. Data analysis uses the Product Moment formula and is followed by a significant correlation with the distribution. The results of this study obtained the coefficient rcount = 0.96 > rtable = 0.497 (Hypothesis accepted) and the correlation test (distribution) showed tcount = 12.82 > rtable = 2.1448 Then Ho was rejected Ha was accepted (significant) and where the results of testing the hypothesis the value of r were 0.96 and where the results of the determination index are 92.16%. From the results of this study, it was concluded that there was a significant contribution between wrist flexibility and smash accuracy in volleyball games for Rajawali club athletes, Pelangiran district, Indragiri downstream. And both variables have very strong data interpretation.